Associations of APOE ε4 With Health and Financial Literacy Among Community-Based Older Adults Without Dementia. (12th May 2016) - Stewart, Christopher C; Boyle, Patricia A; James, Bryan D; Yu, Lei; Han, S Duke; Bennett, David A
Abstract: Objectives: Older adults often exhibit low health and financial literacy, but the reasons why remain unclear. One possibility is that those older adults at high risk for developing dementia demonstrate low literacy even in the absence of marked cognitive impairment. We therefore examined associations of health and financial literacy with the APOE ε4 allele, the chief genetic risk factor for Alzheimer's disease, among older adults without dementia. Method: Participants were 487 older adults without dementia enrolled in the Rush Memory and Aging Project (mean age = 83, mean years of education = 15, 77% female, 91% non-Hispanic White). Participants underwent APOE genotyping and assessments of cognition, health literacy, and financial literacy. Health and financial literacy scores were also averaged into a total literacy score. Results: ε4 was associated with lower total and health literacy, with a trend toward an association with lower financial literacy, after adjustment for age, sex, and education. Associations of ε4 with lower total and health literacy persisted after further adjustment for global cognitive function and 5 specific cognitive domains. Discussion: ε4 affects literacy even in the absence of clinical dementia and does so relatively independent of performance on traditional cognitive tests.